2018
DOI: 10.1186/s12933-018-0763-3
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and platelet hyperactivity in type 2 diabetes mellitus: molecular insights and therapeutic strategies

Abstract: The incidence and prevalence of diabetes mellitus is rapidly increasing worldwide at an alarming rate. Type 2 diabetes mellitus (T2DM) is the most prevalent form of diabetes, accounting for approximately 90–95% of the total diabetes cases worldwide. Besides affecting the ability of body to use glucose, it is associated with micro-vascular and macro-vascular complications. Augmented atherosclerosis is documented to be the key factor leading to vascular complications in T2DM patients. The metabolic milieu of T2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
363
1
23

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 533 publications
(450 citation statements)
references
References 245 publications
(258 reference statements)
8
363
1
23
Order By: Relevance
“…The upregulated MAPK pathway and downregulated eNOS were found in insulin resistance. 33 In this study, we also found reduced eNOS activity in high-glucose-treated EA.hy926 endothelial cells. Here, we found downregulated eNOS activity in EA.hy926 cells treated with supernatants from Corin-siRNA-transfected HK-2 cells, which was rescued by ANP and GSNO, indicating a crucial role of renal Corin-ANP and endothelial NO signaling in endothelial biology.…”
Section: Xue Et Alsupporting
confidence: 69%
“…The upregulated MAPK pathway and downregulated eNOS were found in insulin resistance. 33 In this study, we also found reduced eNOS activity in high-glucose-treated EA.hy926 endothelial cells. Here, we found downregulated eNOS activity in EA.hy926 cells treated with supernatants from Corin-siRNA-transfected HK-2 cells, which was rescued by ANP and GSNO, indicating a crucial role of renal Corin-ANP and endothelial NO signaling in endothelial biology.…”
Section: Xue Et Alsupporting
confidence: 69%
“…This parameter responds positively to glycaemic control only in individuals with T1DM, while individuals with T2DM have a higher number of large platelets which display increased platelet reactivity [159,168,169]. Thus, in individuals with diabetes, platelets are more active, leading to increased adhesion, activation and aggregation and the increased production of platelet-derived microparticles [6,159]. Collectively, these changes result in an increased triggering of thrombus formation and an increased release of pro-coagulatory molecules by platelets such as Ca 2+ , Zn 2+ , fibrinogen, vasoconstrictors and oxidative reactive species which increase coagulation and the atherosclerotic process in both T1DM and T2DM (Figure 4) [159].…”
Section: Platelet Hyper-activationmentioning
confidence: 99%
“…For example, several coagulatory defects are observed in individuals with T1DM or T2DM. Indeed, the vascular endothelium is altered in individuals with both these types of diabetes, and so hypertension, premature atherosclerosis and more extensive vascular diseases can be found in affected individuals compared to the general population, thus also increasing their risk of plaque rupture (in the case of atherosclerosis) and thrombus formation [4][5][6]. Furthermore, in individuals with diabetes, platelets are hyper-reactive, giving rise to increased activation of prothrombotic factors and decreased fibrinolysis which results in an increased risk of thrombosis [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…These data were surprising even for the authors themselves, the hyper coagulable status of diabetic patients being well known. However it seems that the risk of postoperative bleeding in such cases is rather related to a poorer immediately wound healing (typical for diabetic patients), the other factors such as hyper-reactive platelets, reduced fibrinolysis and increased plasminogen activator I inhibitor (which are responsible for the hyper-coagulable status) being not activated during the first hours postoperatively (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%